2010
DOI: 10.1016/j.foodcont.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and self-reported practices of food service staff in nursing homes and long-term care facilities

Abstract: a b s t r a c tThe aim of this study was to investigate knowledge, attitudes and practices of food service staff in nursing homes and long-term care facilities for the elderly in Sicily, Italy. Association with some demographic and work-related variables was also investigated. This survey provides information and outlines many complex questions concerning the basics of food hygiene. Education level, length of service in the employment and attending courses on food hygiene influenced the knowledge, attitudes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
24
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 27 publications
7
24
0
5
Order By: Relevance
“…Thus, identification of deficient practices should lead to the implementation of effective training methods for food handlers in food service systems. The results of several studies have confirmed that training of food handlers can be effective (6,47,56). However, training should be repeated over time to overcome the reluctance of food handlers to apply the acquired knowledge (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, identification of deficient practices should lead to the implementation of effective training methods for food handlers in food service systems. The results of several studies have confirmed that training of food handlers can be effective (6,47,56). However, training should be repeated over time to overcome the reluctance of food handlers to apply the acquired knowledge (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, food safety and quality management systems must be in place to ensure that such meals do not compromise public health (24). Food safety measures have been focused on training of food handlers in appropriate hygiene practices and on improving the sanitary quality of meals (6,47,56). The use of checklists and/or questionnaires in food catering services is highly valuable for monitoring of hazard analysis and critical control point (HACCP) systems (41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The measures include the use of International Organization for Standardization (ISO) method 9001, Total Quality Management (TQM), and hazard analysis critical control point (HACCP) (Aruoma, 2006 Many studies, for instance, Osimani, Aquilanti, Babini, Tavoletti, & Clementi (2011) suggest emphasizing preventative food safety measures to combat outbreaks. The emphasis on appropriate hygiene practices for food safety has been for ready-to-eat meals, water sources, contact surfaces, knowledge and attitudes, and effective hygiene intervention strategies (Buccheri et al, 2010;Holvoet, Jacxsens, Sampers, & Uyttendaele, 2012;Lahou, Jacxsens, Daelman, Van Landeghem, et al, 2012;Michaels et al, 2004;Murphy, DiPietro, Kock, & Lee, 2011;Tang & Fong, 2004). Preventative measures for hygiene has also been done through microbial research (Balzaretti & Marzano, 2012;Lahou, Jacxsens, Daelman, Landeghem, et al, 2012;Rodriguez, Valero, G. D. Posada-Izquierdo, et al, 2011).…”
Section: Hygiene Practicesmentioning
confidence: 99%
“…To date, a number of studies have been done concerning the knowledge, attitudes and practices among food handlers (Buccheri et al, 2010;Jevsnik, Hlebec, & Raspor, 2008;Manning, 1994;Omemu & Aderoju, 2008;Ramsay & Messersmith, 2001;Toh & Birchenough, 2000;Toku, Ekuklu, Berberoglu, Bilge, & Dedeler, 2009), consumers (Sanlier, 2009;Unusan, 2007;Wilcock, Pun, Khanona, & Aung, 2004) and students (Kolodinsky, HarveyBerino, Berlin, Johnson, & Reynolds, 2007;Sangiah, Mundende, & Solomon, 1996;Sharif & Al-Malki). Despite this, information about physicians' knowledge, attitudes and practices concerning foodborne diseases and surveillance has not been available.…”
Section: Introductionmentioning
confidence: 99%